A new high capacity steganography based on bit-inverting method in DWT domain - Azaminezhad, Mahnoosh Sadat; Bidgoli, Amir Massoud (Journal of Advanced Computer Science & Technology, 2014)
Steganography is a technique which embeds the secret messages in the cover image and transmitted in such a way that the existence of information is undetectable. In this paper, we present a new technique that consists of two encoding algorithm such as Huffman encoding and bit inverting algorithm. In this technique, we proposed a modified secure and high capacity based steganography scheme of hiding a secret message such as text or image into a cover image. Our simulation results show that the algorithm has a good perceptual invisibility and high capacity in addition to be secure. Keywords: Bus Inverting, Discrete Wavelet Transform (DWT), Huffman Coding, Steganography, Wavelet.